#PennySparrow and South African race conflicts online : evaluating Twitter as a democratic public sphere - Dyke-Beyer, Bronwen Heather (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--University of Stellenbosch, 2018.